Noções de cosmologia no ensino médio : o paradigma criacionista do Big Bang e a inibição de teorias rivais - Oliveira, Jorge Henrique Lopes de (2006)
Cosmology grounds physics as a whole, but it is not explicitely shown to the student, and many times, it is ignored on the teacher's discourse, since it is not clear on learning materials, neither in High school nor in college. Cosmology, as a unifying discipline, shows itself as an ideal scenario to micro and macro cosmos discussion, from beginning (if there is such a thing) or to the end of the entire physical world. Thus, learning which is the space dedicated to it on physics manuals and what is the discussion proposal (paradigmatic or dialetic) on the theories comparison that seek to trace notions about the Cosmos, is the aim of part of this research. What we intend to reaffirm on this dissertation is that the knowledge on the physical world is or was produced by social subjects who live or lived at a certain historic context, therefore, being part of the human social culture, and this way, it is a right of the students to get acquantated to it and participate on its construction. This study will be presented in two unities. On the first, we will focus on metaphors and analogies about Cosmology present on the discourse of 63 High school and preparatory-college students, as well as on the discourse of physics teachers, searching to understand how theses contents appear at the classroom and if they are or not associated to the teaching of Modern and Contemporary Physics. Moreover, we will evaluate Cosmology notions present on didatic books and paradidatic used on the teaching of physics in High school, looking into identifying topics contemplated is its approach; and, as a last unit's chapter, we will review metaphoric and analogical notions about the Cosmos, criation's concept, building a comparative chart between old-aged mythological narrations and contemporary scientific descriptions by the clergy, philosophers and scientists, emphasasing the segregating charater of science as its peers do not follow the main-stream discourse stated by the so-called "normal science", paradigmatic, postulated by the Academy.